Improving the photostability of fluorescent dyes by polymer nano‐insulating layer. Issue 6 (13th September 2021) - Zhao, Yingshi; Song, Qinyong; Lin, Yuebin; Chu, Feng; Wei, Yanchun; Liu, Sen; Pan, Changjiang; Quan, Li; Wang, Yiqing
Abstract: Fluorescein is a traditional organic fluorescent dye that has the disadvantage of agglomeration‐induced fluorescence quenching and photobleaching due to its large hydrophobic conjugate π‐π system, which makes them have limitations in many fields of application. A method of polymer modification is revealed to address this issue. In this study, fluorescein molecules were modified by polycaprolactone (PCL) to obtain PCL grafting fluorescein (Px F), and subsequently assembled with PEG‐PCL to obtain fluorescent nanoparticles (PPxF). PPxF would realize long term cellular fluorescence imaging. PCL polymerization induces self‐assembly, which effectively avoids fluorescence quenching caused by fluorescent molecules aggregation, and at the same time well inhibit the energy transfer with oxygen to improve photostability. This method is a good way to improve the fluorescence properties of fluorescent dyes, to be suitable for all traditional organic fluorescent dyes to greatly improve their fluorescence and hydrophilic properties and enhance their application fields. Abstract : Polycaprolactone (PCL) polymerization induces self‐assembly, which effectively avoids fluorescence quenching caused by fluorescent molecules aggregation, and at the same time well inhibit the energy transfer with oxygen to improve the photostability. This method is a good way to improve the fluorescence properties of fluorescent dyes.